How do Women Prepare for Pregnancy? Counceling and Giving Folic Acid in Woman of Reproductive Age - Dahlan, Febry Mutiariami; Aulya, Yenny; Safaringga, Miranie (International Journal of Community Services, 2023)
Background: A healthy pregnancy requires physical and mental preparation from everymother. Healthy pregnancy planning should be done before pregnancy. A well-plannedpregnancy process will have a positive impact on the condition of the fetus and thephysical and psychological adaptation of the mother for the better. Folic acid is anessential nutrient required for DNA replication directed at cell proliferation. Folic acid isactivated by the MTHFR gene through an enzymatic reaction. Folic acid can be found infoods as well as in supplements. The demand for folate increases during pregnancybecause it is necessary for the growth and development of the fetus.. Pregnant womenneed extra folic acid about 0.4 mg per day in normal cases and high-risk (previouslyaffected) pregnancies this dose is recommended for 1-3 months before conception. Objective: The purpose of this service is to anticipate high-risk pregnancies by preparingwomen of reproductive age by providing counseling on healthy pregnancy preparationand giving folic acid tablets. Method: The activity was held on April 18, 2013 at BPM I, Pondok Jaya Sub District,Cipayung District, Depok City. Result: The implementation from the midwife went smoothly and received enthusiasmfrom the activity participants.Conclusion: It is hoped that women of healthy reproductive age can get more knowledgerelated to preparing for a healthy pregnancy so that later they will be ready for theirpregnancy and babies born healthy.